Wind farm site selection considering turbulence intensity. (1st December 2021) - Asadi, Meysam; Pourhossein, Kazem
Abstract: Selecting a suitable site is a critical step in wind energy projects. In this regard, using appropriate decision criteria plays a significant role. Turbulence intensity is one of the main characteristics of airflow that affects the power production and lifespan of wind turbines. Therefore, it is considered as a wind site selection criterion in this paper. The present paper formulates the effect of turbulence on both power production and lifespan of wind turbines via an equivalent wind power density (WPDeq ) function, to use it in the wind site selection process. To implement the proposed methodology, 88 wind sites in Iran have been studied. The results reveal the significant effect of turbulence on the site selection process as some sites have changed their rank up to 8 grades considering turbulence intensity in the siting process. To consider the turbulence intensity as an independent criterion to use it in multi-criteria decision-making methods, its relative importance (weight) have to be calculated. Sensitivity analysis shows that, on average, the relative importance of turbulence intensity over wind power density can be approximated as 1/5. Researchers can quickly consider turbulence intensity in siting process incorporating its weight in the pairwise comparison matrix of multi-criteria decision–making. Highlights: The effect of turbulence intensity on wind site selection was studied systematically. Studying 88 sites shows the significant impact of turbulence on wind site selection. Relative importance of turbulence criterion was estimated using sensitivity analysis.